Achalasia, from diagnosis to treatment. (2nd January 2023) - Ribolsi, Mentore; Andrisani, Gianluca; Di Matteo, Francesco Maria; Cicala, Michele
ABSTRACT: Introduction: Achalasia is an uncommon esophageal motility disorder and is characterized by alterations of the motility of the esophageal body in conjunction with altered lower esophageal sphincter (LES) relaxation. The clinical presentation of patients with achalasia may be complex; however, the most frequent symptom is dysphagia. The management of patients with achalasia is often challenging, due to the heterogeneous clinical presentation. Areas covered: The diagnosis and management of achalasia has significantly improved in the last years due to the growing availability of high-resolution manometry (HRM) and the implementation in the therapeutic armamentarium of new therapeutic endoscopic procedures. Traditional therapeutic strategies include botulinum toxin injected to the LES and pneumatic balloon dilation. On the other hand, surgical treatments contemplate laparoscopic Heller myotomy and, less frequently, esophagectomy. Furthermore, in the last few years, per oral endoscopic myotomy (POEM) has been proposed as the main endoscopic therapeutic alternative to the laparoscopic Heller myotomy. Expert opinion: Diagnosis and treatment of achalasia still represent a challenging area. However, we believe that an accurate up-front evaluation is, nowadays, necessary in addressing patients with achalasia for a more accurate diagnosis as well as for the best treatment options.